2021
DOI: 10.1093/cid/ciab562
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of Candidemia During the Coronavirus Disease 2019 (COVID-19) Pandemic

Abstract: Background The COVID-19 pandemic has resulted in unprecedented healthcare challenges, and COVID-19 has been linked to secondary infections. Candidemia, a fungal healthcare-associated infection, has been described in patients hospitalized with severe COVID-19. However, studies of candidemia and COVID-19 co-infection have been limited in sample size and geographic scope. We assessed differences in patients with candidemia with and without a COVID-19 diagnosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
4
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 25 publications
5
89
4
3
Order By: Relevance
“…The literature search identified 41 articles reporting cases of yeast fungemia during COVID-19 [2,14,15,21,29,30,36,44,45,51,54,60,; most of them were from Italy (9, 22%), followed by the USA (6, 14.6%) and Brazil (4, 9.8%).…”
Section: Candidemia and Other Yeast Fungemiamentioning
confidence: 99%
See 2 more Smart Citations
“…The literature search identified 41 articles reporting cases of yeast fungemia during COVID-19 [2,14,15,21,29,30,36,44,45,51,54,60,; most of them were from Italy (9, 22%), followed by the USA (6, 14.6%) and Brazil (4, 9.8%).…”
Section: Candidemia and Other Yeast Fungemiamentioning
confidence: 99%
“…Twenty-five observational studies reported 360 cases of candidemia, with an average incidence of 3.8% [2,14,15,21,29,30,36,44,45,51,54,60,[124][125][126][127][128][129][130][131][132][133][134][135][136] (Table 5; detailed information about the individual studies is given in Table S5). More than 80% of the patients had classic risk factors (an in-dwelling vascular catheter and broad-spectrum antibiotics), but only 21.4% received total parenteral nutrition.…”
Section: Observational Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…CAC has been described globally at varying incidences (<1 to 23.5%), mostly presenting as candidaemia 1–2 weeks post admission, caused primarily by Candida albicans and Candida glabrata , although outbreaks caused by multidrug-resistant C. auris continue to be reported [ 3 , 10 , 18 ▪ , 40 42 ]. Diagnosis is primarily through the recovery of Candida spp.…”
Section: Diagnosis Of Coronavirus Disease-2019-associated Candidosismentioning
confidence: 99%
“…Although Candida risk/colonization scores have shown potential for identifying patients at increased risk of IC, the significant number of clinical interventions and the necessary duration of admission in the ICU mean that critical-care COVID-19 patients are likely exposed to prolonged risk of invasive candidosis [ 18 ▪ , 40 , 49 , 50 ]. It remains unclear what combination of tests will prove optimal for the diagnosis of invasive candidosis in either the COVID-19 or non-COVID-19 population, but a likely combination of molecular, serological and conventional testing will cover the range of targets potentially available in cases of invasive candidosis and when all tests are negative invasive candidosis will be unlikely [ 51 ].…”
Section: Diagnosis Of Coronavirus Disease-2019-associated Candidosismentioning
confidence: 99%